Relação entre o estado nutricional e hábitos alimentares de pacientes bariátricos com e sem acompanhamento nutricional durante a pandemia de COVID19 no Brasil - OLIVEIRA, Katarina Marcelino de (2023)
The objective of the study was to evaluate the association between selfreported nutritional status, eating habits and nutritional monitoring of bariatric patients in the context of the COVID19 pandemic in Brazil. This is a crosssectional, descriptive and analytical study with bariatric patients during the COVID19 pandemic in Brazil from August 2018 to February 2022. The form was applied using Google Forms with 34 questions divided into 6 axes: socioeconomic data, financial situation, anthropometric data, bariatric surgery, eating habits during the pandemic and food consumption markers. For statistical analysis, the Kolmogorov smirnov test was used to test the normality of distributions; the paired Student's t test was applied to the independent variables; and Pearson's chisquare test with adjusted residual analysis to test the association between categorical variables, adopting a significance level of alpha at 5% (p<0.05). 412 patients participated in the research. Among the results, it is noteworthy that patients with nutritional monitoring had a higher BMI during the pre pandemic period and higher consumption of fresh fruits, while patients without nutritional monitoring had a positive association with higher consumption of ultraprocessed foods and the habit of skipping 6 meals per day, in addition to nonconsumption of fresh fruit, was positively associated with high body mass index. In view of this, it is evident that the COVID19 pandemic caused impacts on these individuals, with changes in anthropometric data and eating habits.